Atopy and allergy following solid organ transplantation: A 15‐year experience. (30th January 2023) - Roberts, Amin J; Lim, Alicia; Bishop, Jonathan R; Gane, Ed; Rakhmanova, Elizaveta; Wong, William; Evans, Helen M
Abstract : Aim: There are increasing reports of atopy/allergy following solid organ transplantation, especially paediatric liver transplantation (LT) with minimal New Zealand (NZ) data. We describe the prevalence of transplant‐acquired atopy and allergy (TAA) in NZ paediatric liver transplant recipients, compared to paediatric kidney and adult liver transplants. Methods: TAA focussed health questionnaires were sent to patients selected from the NZ transplant registry (transplanted between January 2003 and December 2017). Demographic and clinical data were also obtained from electronic health records and follow‐up phone calls. Results: A total of 232 patients (62% male) participated (111 adult liver, 82 paediatric liver, 39 paediatric kidney transplant recipients). Tacrolimus was primary immunosuppression for all LT patients; with combined tacrolimus, mycophenolate and corticosteroids for kidney transplants. The number of patients who developed TAA was significantly higher ( P < 0.001) in the paediatric LT group (36/82, 44%) compared to adult liver (12/111, 11%) and paediatric kidney transplants (4/39, 10%). Eczema was most common (73%), then IgE‐mediated food allergy (FA, 33%), allergic rhinitis (19%) and asthma (17%). Six paediatric LT recipients developed eosinophilic oesophagitis (EoE). Egg was the most common allergen in the IgE‐mediated FA group. TAAs were severe enough to warrant a switch from tacrolimus to another agent in seven paediatric LT patients. For paediatric LT patients, female gender and younger age at transplant were risk factors for developing TAA. Conclusions: TAA is common in paediatric liver transplant recipients, with female gender and younger age at transplant being risk factors identified. This highlights the need for detailed atopic and allergy history to be incorporated in all pre‐transplant assessments.